Construction project manager's pocket book - Cartlidge, Duncan P. (Abindgon, Oxon ; New York : Routledge, 2020)
"The second edition of the Construction Project Manager's Pocket Book maintains its coverage of a broad range of project management skills, from technical expertise to leadership, negotiation, team building and communication"--
OCLC-licensed vendor bibliographic record.
Keywords: Construction industry -- Management -- Handbooks, manuals, etc; Project management -- Handbooks, manuals, etc; Building -- Superintendence -- Handbooks, manuals, etc; BUSINESS & ECONOMICS / Project Management